(untitled) (The Research of Medical Science Review, 2024)
This study aimed to explore the proximate composition, satiety and blood glucose response of cookies enriched with carrot pomace. The cookies were prepared using wheat flour (WF) as the base ingredient, and different percentages of carrot pomace (25%, 35%, and 45%) were incorporated into the formulations. The control group consisted of cookies that are made solely from WF. The proximate composition analysis revealed significant differences (p<0.05) between the cookies in term such as ash, crude fat, crude protein, moisture, crude fiber, and carbohydrates. The addition of carrot pomace resulted in an upsurge in moisture content, with the highest value observed in CP45 (5.88±0.13%). Ash content also showed increased with the substitution of CP, with CP45 having the highest percentage (4.98±0.07%). The crude protein content showed a gradual increase as the percentage of carrot pomace increased, with CP45 having the highest value (8.90±0.11%). The crude fat content varied among the cookies, with CP35 (2.51±0.01%) having the highest value. The cookies containing carrot pomace exhibited higher crude fiber content, with CP45 (10.66±0.33%) having the highest value. Conversely, the percentage of carbohydrates decreased as the percentage of carrot pomace increased, with CP45 (67.32±0.60%) having the lowest value. Sensory evaluation of the cookies demonstrated significant differences (p<0.05) in terms of appearance, flavor, texture and whole acceptance. CP45 received the highest scores in all sensory attributes, indicating better acceptability. The study subjects' baseline measurements showed that they were healthy individuals with mean height, weight, age, and BMI of 175.12±5.24 cm, 72.85±6.37 kg, 25.67±1.05 years, and 23.41±2.22 kg/m², respectively. The satiety analysis revealed significant differences (p<0.05) in the subjects' satiety levels before breakfast, with CP35 (1.70±1.65) and CP45 (1.40±0.65) scoring higher than the control group (1.45±0.60). However, no considerable variation was observed in the satiety levels after breakfast among the different groups of cookies. The blood glucose response of the study subjects was assessed at five different time points (0, 15, 30, 45, and 60 minutes) after consumption of the test cookies. The results revealed that significant differences (p<0.05) at 60-minute mark, where the control group had the highest blood glucose level (103.35±4.98 mg/dl) compared to the other groups. CP45 (95.70±3.94 mg/dl) exhibited the lowest blood glucose level at this time point.